Reconstructing Consumer Protection through Product Liability Reform from a Tort Law Perspective - Faisal Santiago; Amalia Sari; M. Saleh; Makkamadin Aras Nai (JURNAL AKTA, 2026)
This study aims to examine and reconstruct Indonesia’s product liability regulations from a Tort Law Perspective in order to strengthen effective consumer protection in contemporary commerce. The research is grounded in the problem that existing regulatory frameworks, particularly those contained in the Civil Code and Law Number 8 of 1999 concerning Consumer Protection, remain general in character and predominantly fault-oriented, thereby limiting consumers’ ability to obtain compensation for losses caused by defective products. Such a framework is increasingly inadequate in responding to complex distribution chains, digital transactions, and modern market risks. This study employs a normative juridical method using statutory and conceptual approaches. The statutory approach analyzes relevant legislative provisions through systematic and teleological interpretation, while the conceptual approach examines core tort doctrines such as strict liability, vicarious liability, and duty of care within comparative legal discourse. The novelty of this research lies in its systematic reconstruction model that integrates modern tort principles into Indonesia’s product liability regime, moving beyond a purely fault-based paradigm toward a risk-allocation and consumer-oriented framework. The findings demonstrate that incorporating strict liability standards, expanding accountability through vicarious liability, and reinforcing duty of care obligations would create a more balanced, preventive, and justice-oriented liability system. Such reform is essential to enhance legal certainty, improve access to remedies for consumers, and harmonize national regulations with global developments in tort law.